Modeling Recurrence in Idiopathic Subglottic Stenosis With Mobile Peak Expiratory Flow. (26th July 2021) - Kimura, Kyle; Du, Liping; Berry, Lynn D.; Huang, Li‐Ching; Chen, Sheau‐Chiann; Francis, David O.; Gelbard, Alexander; ,
Abstract : Objectives/Hypothesis: We sought to establish normative peak expiratory flow (PEF) data for patients with idiopathic subglottic stenosis (iSGS), evaluate whether immediate changes in PEF after a procedure predict long‐term treatment response, and test if a decline in longitudinal PEF is associated with disease recurrence. Study Design: International, prospective, 3‐year multicenter cohort study of 810 patients with untreated, newly diagnosed, or previously treated iSGS. Methods: iSGS patients consented and enrolled in the North American Airway Collaborative (NoAAC) iSGS 1000 cohort recorded PEF data on a mobile smartphone app. Cox regression tested the associations between the magnitude of postoperative PEF improvement and longitudinal 90‐day PEF decline with the risk of disease recurrence. Results: Within the NoAAC iSGS 1000 cohort, 810 patients participated in a 3‐year prospective study comparing surgical treatment efficacy and 385 had appropriate PEF measurements and follow‐up data. Of those patients, 42% (161/385) required at least one operation during study follow‐up. The mean PEF preceding operative intervention was 241 L/min (95% confidence interval [CI]: 120–380) corresponding to a predicted PEF of 52%. The mean increase in PEF following a procedure was 111 L/min (95% CI: 96–125 L/min). Interestingly, the magnitude of immediate PEF improvement was not predictive of disease recurrence (hazard ratio [HR] for 100 L/min increase = 0.90, 95% CI: 0.60–1.00). However, recurrence was associated with the magnitude of PEF decline over 90 days (30% vs. 10% decline, HR = 2.2, 95% CI: 1.5–3.0). Conclusions: We provide normative PEF data on a large iSGS patient cohort. The degree of PEF improvement immediately after surgery was not associated with a longer procedure‐free interval. However, a 30% decline in PEF over 90 days was associated with elevated risk of disease recurrence. Level of Evidence: 2 Laryngoscope, 131:E2841–E2848, 2021